Exploratory research of intersubjective sense of recognition (Research, Society and Development, 2020)
Objective: The Recognition Experience is an existential dimension that contributes to the psychological health of people, as it benefits the realization of creativity, self-contact, solidarity, action in a capable way, legal recognition, self-respect and self-respect. another, this understanding constituted the theoretical background of the articulation with the perceptions of the collaborators of the exploratory qualitative research carried out in a Federal University of the Northern Region. Method: We focused on the recognition experience for six men and five women aged 20 to 70, with higher education. A questionnaire with open questions was applied whose discursive textual analysis focused on the search for the senses of recognition. Results:  five men and four women said they felt recognized, and one man who did not, due to his race, was often denied. Still, perceptions of recognition mentioned acts of support; self-knowledge and acceptance. We conclude that the findings allude that the experience of non-recognition is an example of denial in social contexts. Research reports are promising for the clinical practice of Gestalt therapists interested in intersubjective recognition, overcoming denial factors, dialogic listening and understanding of contact dysfunctions that favor neurotic adjustments and self-ignorance.